Local Bilingües - Zungarococha - Centro de Estudios Teológicos de la Amazonía (CETA) (My University, 1999)
SPANISH: Local Bilingües, ubicado en en centro de Formación de Maestros Bilingües de la Amazonia Peruana (FORMABIAP) - Zungarococha
ENGLISH: Local Bilingües, located in the Bilingual Teacher Training Center of the Peruvian Amazon (FORMABIAP) - Zungarococha.

SPANISH: Local Bilingües, ubicado en en centro de Formación de Maestros Bilingües de la Amazonia Peruana (FORMABIAP) - Zungarococha
ENGLISH: Local Bilingües, located in the Bilingual Teacher Training Center of the Peruvian Amazon (FORMABIAP) - Zungarococha.
Local Bilingual - Zungarococha
Keywords: Iquitos (Perú)|~|Architecture|~|Rural|~|Amazon|~|Nature|~|Jungles|~|Paisajes|~|Iquitos (Perú)|~|Iquitos (Perú)|~|arquitectura|~|rural|~|naturaleza|~|junglas